Expansile Endocervical Crypt Involvement by CIN2 – 3 as a Risk Factor for High Grade Cytology Recurrence After Cold Coagulation Cervical Treatment - Papoutsis, Dimitrios; Underwood, Martyn; Williams, Joanna; Parry-Smith, William; Panikkar, Jane (Geburtshilfe und Frauenheilkunde, 2020)
Introduction To determine whether expansile endocervical crypt involvement (ECI) on pretreatment cervical punch biopsies is a risk factor for high grade cytology recurrence in women following cold coagulation for cervical intraepithelial neoplasia (CIN).Materials and Methods This was a secondary analysis on the results of an observational study of women who had a single cold coagulation cervical treatment between 2001 – 2011 and who were followed up for cytology recurrence. Women with a previous cervical treatment were excluded.Results 559 women were identified with a mean age of 28.7 ± 6.2 years. Expansile and non-expansile ECI were identified in 5.4 and 4.3% of women, respectively. The proportion of women with high grade cytology recurrence was 10% for those with expansile ECI and 2.3% for those without. Multivariate analysis showed that women with expansile ECI when compared to those without, had a four-fold greater risk for high grade cytology recurrence (HR = 4.22; 95% CI: 1.10 – 16.29, p = 0.036). There was no significant association found between non-expansile ECI and overall or high grade cytology recurrence. The increased biopsy depth and the CIN3 grade of pretreatment cervical punch biopsies were significantly associated with greater odds for the detection of expansile ECI. We calculated that the optimal-cut off of pretreatment cervical punch biopsy depth for the detection of expansile ECI was 4 mm (sensitivity: 73.3%; specificity: 55.1%).Conclusions Expansile ECI is a risk factor that increases the likelihood of high grade cytology recurrence following cold coagulation. Deeper pretreatment cervical punch biopsies need to be taken so as not to miss expansile ECI prior to ablative treatment.
Keywords: cold coagulation; endocervical crypt involvement; cytology recurrence; CIN